Role of fetal autopsy as a complementary tool to prenatal ultrasound. (November 2014) - Godbole, Koumudi; Bhide, Vijayshri; Nerune, Savitri; Kulkarni, Aparna; Moghe, Mrinalini; Kanade, Asawari
Abstract Aim: To correlate and compare prenatal ultrasound with fetal autopsy examination to detect structural births defects and provide specific diagnoses. Methods: 141 second trimester fetuses (<20 weeks and <500 g) where pregnancy was terminated for structural birth defects and/or severe intra-uterine growth restriction (IUGR) or intra-uterine death, referred to our tertiary care private, teaching hospital were examined by a team of experienced pathologist and clinical geneticist. Findings of pathology examination were compared to those provided by ultrasound examination. Results: A total of 301 structural abnormalities were noted. Specific etiology was identified or syndromic diagnosis was possible in 57/141 (40.4%) cases. The maximum number of systemic anomalies (45/301, 14.95%) was noted in the central nervous system (CNS). CNS anomalies were most commonly associated with facial dysmorphism including cleft lip/palate etc. There was a complete agreement between ultrasound and autopsy findings in 41/141 (29.07%) cases, additional information that did not influence the final diagnosis and/or counseling was obtained by autopsy in 65/1416 (46.09%) cases, while additional information that influenced the final diagnosis and/or counseling was provided by autopsy in 35/141 (24.82%) cases. Conclusion: Fetal autopsy serves as a complementary tool to fetal ultrasound due to its ability to pick up minor anomalies and/or anomalies that were missed on ultrasound. It may be routinely performed as an attempt to reach a specific diagnosis and offer appropriate counseling to couples, following pregnancy termination for fetal anomalies.